1976
DOI: 10.1093/ajcp/66.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Intranuclear Inclusions in Plasma Cells and Lymphocytes from Patients with Monoclonal Gammopathies

Abstract: Ultrastructural studies of intranuclear inclusions in plasma cells and lymphocytes from patients with different forms of monoclonal gammopathies are presented. The inclusions occurred as two distinct morphologic and ultrastructural types. In three patients, two with IgA myeloma and one with Waldenström's macroglobulinemia, the inclusions were variably PAS-positive in routine sections and composed of electron-light amorphous material ultrastructurally. In one patient with an IgG monoclonal gammopathy, the plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
2

Year Published

1980
1980
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 0 publications
2
17
0
2
Order By: Relevance
“…Although FL has been occasionally described to display plasmacytic differentiation and contain rare Dutcher bodies in individual cases [7,30], those with extensive Dutcher body formation, as shown in the current study, are extremely rare, and to the best of our knowledge, only a single case was reported by our group in the English literature [28]. Although a Dutcher body is morphologically characterized by a round, usually single intranuclear inclusion, and a Russell body is considered as its cytoplasmic counterpart, both have been illustrated as globules of accumulated Ig in the rough endoplasmic reticulum [19]. In contrast to Russell bodies, Dutcher bodies are formed by an invagination of Ig-rich cytoplasm or perinuclear cisternae of rough endoplasmic reticulum into the nuclear compartment per electronic microscopic studies [19,24] and are, thus, considered to be pseudonuclear inclusions.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…Although FL has been occasionally described to display plasmacytic differentiation and contain rare Dutcher bodies in individual cases [7,30], those with extensive Dutcher body formation, as shown in the current study, are extremely rare, and to the best of our knowledge, only a single case was reported by our group in the English literature [28]. Although a Dutcher body is morphologically characterized by a round, usually single intranuclear inclusion, and a Russell body is considered as its cytoplasmic counterpart, both have been illustrated as globules of accumulated Ig in the rough endoplasmic reticulum [19]. In contrast to Russell bodies, Dutcher bodies are formed by an invagination of Ig-rich cytoplasm or perinuclear cisternae of rough endoplasmic reticulum into the nuclear compartment per electronic microscopic studies [19,24] and are, thus, considered to be pseudonuclear inclusions.…”
Section: Discussionmentioning
confidence: 49%
“…Although a Dutcher body is morphologically characterized by a round, usually single intranuclear inclusion, and a Russell body is considered as its cytoplasmic counterpart, both have been illustrated as globules of accumulated Ig in the rough endoplasmic reticulum [19]. In contrast to Russell bodies, Dutcher bodies are formed by an invagination of Ig-rich cytoplasm or perinuclear cisternae of rough endoplasmic reticulum into the nuclear compartment per electronic microscopic studies [19,24] and are, thus, considered to be pseudonuclear inclusions. The reactivity of inclusion bodies to anti-Ig in our cases was consistent with the previous findings and confirmed their nature as Dutcher bodies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations